ADAPTIVE REUSE PADA BIOSKOP DIAN SEBAGAI BANGUNAN CAGAR BUDAYA GOLONGAN A DI KOTA BANDUNG - Vanessa Adinda Rahmadya; Harastoeti Dibyo Hartono (Riset Arsitektur (RISA), 2021)
Abstract- Dian Cinema is an entertainment building in the form of a cinema that was built in 1930 under the name Radio City at that time. Located on Jalan Dalem Kaum no. 58, Bandung, Dian Cinema is the only cinema building left in the Alun - alun area and it is categorized as Group A Cultural Heritage Building in Bandung. In the beginning, Dian Cinema had experienced its heyday by showing a variety of foreign and local films, until it was eventually replaced with a new, more modern cinema concept that made Dian Cinema visitors diminished and eventually closed. The transition of functions in this building continues as a billiard sports venue, a place to sell clothes, rental offices, football sports venues, until now, Dian cinema is run into a vacuum of function. This makes the condition of the building become untreated and unmaintained well. In fact, the use of buildings in the right way can save these buildings and have a positive impact on the surrounding environment. Therefore, the proposed of a new function commonly referred to as adaptive reuse is carried out as one of the conservation act of cultural heritage buildings to maintain its history and existence. The study uses descriptive methods with qualitative analysis and evaluation, by describing the existing condition of the building. After that, it was conducted on the needs of the area in accordance with Bandung City regulations, conservation theory, analysis of the area and buildings, as well as examples of the successful application of adaptive reuse in Indonesia. The results of this study resulted in a new function, the Art Studio and the Performing Gallery which was considered applicable to the Dian Cinema building. The function is chosen based on a series of analysis results such as location, historical value, building characteristics, spatial requirements, to the potential and constraints of the building and area. The existence of new functions in the building is expected to be able to evoke social activities and old historical memories that are starting to fade, increase public knowledge, become an entertainment building and educational tourist destinations, and can participate in maintaining, protecting, and utilizing the existence of Group A Cultural Heritage Buildings in Bandung. Key Words: Adaptive Reuse, Cultural Heritage Building, Bioskop Dian